(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Amruthadi Kashaya is a Ayurvedic formulation mentioned in the book Arogya Kalpadruma for the treatment of Pandu (anaemic syndrome), Kamala (jaundice) and Raktapitha (bleeding disorders). The Yoga contains six drugs namely Amrutha (Tinospora cordifolia), Vasa (Adhatoda vasica), Yashtimadhu (Glycyrrhiza glabra), Tiktha (Solanum anguivi), Ela (Elettaria cardamomum), Pichumantha (Azadirachta indica). This Kashaya is rich in phytoconstituents, such as phenolics, terpenoids, and lipids, which are known for their many biological benefits, including anti-inflammatory, anti-cancer, and antioxidant effects. The purpose of the current study is to use Gas Chromatography Mass Spectrometry (GCMS) analysis to identify the different types of bio molecules that are present in this Kashaya. Kashaya was prepared according to standard protocol. It was concentrated in the rotary vacuum evaporator, and the total soluble solid (TSS) obtained was used for GCMS analysis. The GCMS of Kashaya showed the presence of bio molecules such as 7 Hexadecanoic acid, methyl ester, Methyl tetradecanoate, Diethyl Phthalate, Dodecanoic acid, methyl ester, Methyl stearate, à-Terpineol, Methyl 8-methylnonanoate, 3-Cyclohexene-1-methanol, à, à,4-trimethyl-, acetate, Decanoic acid, methyl ester, 1,6,10-Dodecatrien-3-ol,3,7,11-trimethyl-, (E)-, Ethyl iso-allocholate, Spiro [2,4] hepta-4,6-diene, Butylated Hydroxytoluene, 9-Hexadecenoic acid, methyl ester, (Z) etc. à-Terpineol, 7-Hexadecenoic acid, methyl ester, Butylated hydroxytoluene, Nerolidyl acetate have antioxidant activity likewise some of the bio molecules have anti-inflammatory, antibacterial, anticancer activity. It is concluded that Ayurvedic formulation Amruthadi Kashaya contains many bio molecules having therapeutic actions.